Islamic Education in the Context of the Relationship Between Religion, Cultural Pluralism, and Multicultural Education - Fadliana, Nyayu Afriyani Nur; Idi, Abdullah; Karoma, Karoma (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
This research examines the relationship between religion, cultural pluralism, and multicultural education in the context of an increasingly diverse society. The topic is important for understanding how cultural and religious pluralism affects social interactions and education in Indonesia. This study employs a qualitative approach with literature review and in-depth interviews as data collection techniques. The research instrument consists of interview guides developed based on theories of pluralism and multicultural education. Data analysis is conducted using thematic analysis, identifying patterns and themes from the collected data. The findings reveal that religion and cultural pluralism play a crucial role in shaping multicultural education, both in educational policies and classroom practices. The discussion highlights the importance of integrating multicultural values in education to foster a harmonious and inclusive society. This research contributes to the development of multicultural education theory and provides recommendations for curriculum development that is more sensitive to cultural and religious diversity.